A New Characterization of Compact Sets in Fuzzy Number Spaces - Huan Huang; Congxin Wu (Abstract and Applied Analysis)
We give a new characterization of compact subsets of the fuzzy number space equipped with the level convergence topology. Based on this, it is shown that compactness is equivalent to sequential compactness on the fuzzy number space endowed with the level convergence topology. Our results imply that some previous compactness criteria are wrong. A counterexample also is given to validate this judgment.